Human factors and systems simulation methods to optimize peri-operative EHR design and implementation - Mirette Dubé; Jonathan D. Hron; Susan Biesbroek; Myrna Chan-MacRae; AEliot Shearer; Rocco Landi; Melanie Swenson; Daniel J. Kats; Doreen White; Reilly Birmingham; Lauren Coogle; Jennifer Arnold (Advances in Simulation)
Abstract The increase in adoption of Electronic Health records (EHR) in healthcare can be overwhelming to users and pose hidden safety threats and inefficiencies if the system is not well aligned with workflows. This quality improvement study, facilitated from September 2023–April 2024, aimed to proactively test a new EHR using systems focused simulation and Human factors methods, prior to go-live, in a peri-operative children’s hospital setting to improve safety, efficiency and usability of the EHR. The project was conducted at a large, academic, quaternary care children’s hospital undergoing a transition from one EHR to another. Two cycles of usability testing followed by in situ simulations focused on testing the new EHR with interprofessional peri-operative team members prior to go live. Usability testing, using relevant clinical workflows, was completed over zoom using the EHR “testing” environment with individual care providers across multiple peri-operative roles. In situ simulations were facilitated in the actual peri-operative and Otolaryngology clinic spaces with full interprofessional teams. Qualitative data was collected and summarized through debriefing and recordings of the sessions. Human factors and patient safety principles were integrated throughout the recommendations. A total of 475 recommendations were made to improve the safety, efficiency, usability, and optimization of the EHR. The outcomes included a range of usability and system issues including latent safety threats and their impact on safe and quality patient care. There was a plethora of usability improvements, including some critical issues that were uncovered and mitigated prior to the go live date.